2011
DOI: 10.1029/2010ja015872
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the heliospheric current and plasma sheets with the bow shock: Cluster and Polar observations in the magnetosheath

Abstract: [1] On 12 March 2001, the Polar and Cluster spacecraft were at subsolar and cusp latitudes in the dayside magnetosheath, respectively, where they monitored the passage by Earth of a large-scale planar structure containing the high-density heliospheric plasma sheet (HPS) and the embedded current sheet. Over significant intervals, as the magnetic hole of the HPS passed Cluster and Polar, magnetic field strengths |B| were much smaller than expected for the shocked interplanetary magnetic field. For short periods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…For conditions with δ i,e ≪ 1, guiding center theory describes the particle motion, and the MHD approximation to the generalized Ohm's law applies. A particle species is said to be demagnetized if δ i,e > 1 [ Macmahon , 1965; Vasyliunas , 1975; Scudder et al , 2008; Maynard et al , 2011]. Based on field‐line‐resonance‐ordering considerations, Scudder et al [2008] also demonstrated that δ is more accurately connected to the ratio of the perpendicular electric to magnetic forces experienced by a thermal ion or electron in the plasma's rest frame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For conditions with δ i,e ≪ 1, guiding center theory describes the particle motion, and the MHD approximation to the generalized Ohm's law applies. A particle species is said to be demagnetized if δ i,e > 1 [ Macmahon , 1965; Vasyliunas , 1975; Scudder et al , 2008; Maynard et al , 2011]. Based on field‐line‐resonance‐ordering considerations, Scudder et al [2008] also demonstrated that δ is more accurately connected to the ratio of the perpendicular electric to magnetic forces experienced by a thermal ion or electron in the plasma's rest frame.…”
Section: Discussionmentioning
confidence: 99%
“…Early satellite measurements indicate that the LLBL accounts for <10 kV of the ionospheric cross polar cap potential [ Smiddy et al , 1980; Mozer , 1984]. However, LLBL contributions to the polar‐cap potential may become significantly larger during periods of weak or northward IMF and/or high solar wind velocity [e.g., Sonnerup et al , 2001; Engebretson et al , 1998; Maynard et al , 2011]. Along the distant magnetopause where plasma flow is nearly parallel to the boundary, magnetosheath thermal pressure contributes significantly to force balance.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetosonic waves have long been identified in the solar wind [ Burlaga and Turner , ]. In the HCS, fast‐mode waves have been seen during the HCS/HPS passage in the magnetosheath [ Maynard et al , ]. In our event, a fast‐mode wave packet is found at a current layer associated with a steeped edge of a large‐scale transverse Alfvén wave.…”
Section: Summary and Discussionmentioning
confidence: 56%
“…The waves are associated with an electric field fluctuation as large as 4 mV/m and a magnetic field fluctuation as large as 10 nT. The fluctuation amplitude relative to background field ( δ | B |/| B |) is comparable with fast‐mode waves in Maynard et al []. The correlated fluctuations in magnetic field strength and plasma density are shown in Figure e.…”
Section: Ace and Cluster Observationsmentioning
confidence: 60%
See 1 more Smart Citation